Colour, pleasantness, and consumption behaviour within a meal. - Piqueras-Fiszman, B; Spence, C (2014)
It is often claimed that colour (e.g., in a meal) affects consumption behaviour. However, just how strong is the evidence in support of this claim, and what are the underlying mechanisms? It has been shown that not only the colour itself, but also the variety and the arrangement of the differently-coloured components in a meal influence consumers' ratings of the pleasantness of a meal (across time) and, to a certain extent, might even affect their consumption behaviour as well. Typically, eating the same food constantly or repeatedly leads to a decrease in its perceived pleasantness, which, as a consequence, might lead to decreased intake of that food. However, variation within a meal (in one or several sensory attributes, or holistically) has been shown to slow down this process. In this review, we first briefly summarize the literature on how general variety in a meal influences these variables and the major theories that have been put forward by researchers to explain them. We then go on to evaluate the evidence of these effects based mainly on the colour of the food explaining the different processes that might affect colour-based sensory-specific satiety and, in more detail, consumption behaviour. In addition, we also discuss the overlap in the definitions of these terms and provide additional hypothesis as to why, in some cases, the opposite pattern of results has been observed.